Marketing Strategies to Increase Room Occupancy at Jambuluwuk Oceano Seminyak Hotel - I Gede Arimbawa; Ni Putu Wiwiek Ary Susyarini; Gede Ginaya; Ni Made Rai Sukmawati; Ni Made Sudarmini (International Journal of Travel, Hospitality and Events, 2023)
Purpose: This study aims to see the strengths and weaknesses of internal factors as well as opportunities and threats of external factors and to formulate appropriate marketing strategies in increasing room occupancy rates at a 5-star hotel in Seminyak, Bali. Research methods: Data collection methods used are observation, interviews, questionnaires, and document study. The data analysis technique is descriptive qualitative analysis, IFAS matrix (internal strategy factor), EFAS matrix (external strategy factor), SWOT analysis and SWOT matrix. The method of determining the sample is purposive sampling, namely selecting respondents with certain criteria with 6 respondents. Results and discussion: There are 10 indicators of internal factors that become strengths, 5 indicators of internal factors that become weaknesses, 6 indicators of external factors that become opportunities, and 1 indicator of external factors that become threats. The results of the IE matrix research show that the strategy used is in column I, namely the growth strategy of the company itself. Implication: The SWOT analysis resulted in 8 strategies, namely the SO strategy that can be applied such as increasing collaboration with other offline travel agents and holding activities by utilizing the attractiveness of local (Balinese) culture. Keywords: hotel, room occupancy rate, SWOT, marketing mix.